Self-expandable metal stents for malignant gastric outlet obstruction: A pooled analysis of prospective literature - van Halsema, Emo E (World J Gastroenterol, 2015)
AIM: To provide an overview of the clinical outcomes of self-expandable metal stent (SEMS) placement for malignant gastric outlet obstruction (MGOO). METHODS: A systematic literature search was performed in PubMed of the literature published between January 2009 and March 2015. Only prospective studies that reported on the clinical success of stent placement for MGOO were included. The primary endpoint was clinical success, defined according to the definition used in the original article. Data were pooled and analyzed using descriptive statistics. Subgroup analyses were performed for partially covered SEMSs (PCSEMSs) and uncovered SEMSs (UCSEMSs) using Fisher’s exact test. RESULTS: A total of 19 studies, including 1281 patients, were included in the final analysis. Gastric (42%) and pancreatic (37%) cancer were the main causes of MGOO. UCSEMSs were used in 76% of patients and PCSEMSs in 24%. The overall pooled technical success rate was 97.3% and the clinical success rate was 85.7%. Stent dysfunction occurred in 19.6% of patients, mainly caused by re-obstruction (12.6%) and stent migration (4.3%), and was comparable between PCSEMSs and UCSEMSs (21.2% vs 19.1%, respectively, P = 0.412). Re-obstruction was more common with UCSEMSs (14.9% vs 5.1%, P < 0.001) and stent migration was more frequent after PCSEMS placement (10.9% vs 2.2%, P < 0.001). The overall perforation rate was 1.2%. Bleeding was reported in 4.1% of patients, including major bleeding in 0.8%. The median stent patency ranged from 68 to 307 d in five studies. The median overall survival ranged from 49 to 183 d in 13 studies. CONCLUSION: The clinical outcomes in this large population showed that enteral stent placement was feasible, effective and safe. Therefore, stent placement is a valid treatment option for the palliation of MGOO.